An application of U/Th-series radiotracers to study groundwater transport processes in the surficial and Upper Floridan Aquifer System in central Florida, USA - Baskaran, Mark; Jweda, Jason; Newton, Jeff; Swarzenski, Peter W. (Frontiers in Water, 2026)
U-Th series radionuclides are effective, naturally occurring tracers for studying groundwater transport mechanisms. Dissolution and sorption/desorption processes involving Fe-Mn oxyhydroxides play a major role in the mobility of select trace elements and radionuclides. For example, as radium is strongly bound to manganese oxides in most natural waters, the behavior of Mn in groundwater can be expected to affect Ra adsorption–desorption rates. In this study, the redox state of the aquifer in central Florida was examined to investigate the groundwater mobility of Ra and other trace elements. From a suite of 13 groundwater samples and complementary soil core samples, U/Th parent–daughter disequilibria were utilized to obtain sorption–desorption rate constants for radium. The large observed variability in 222Rn and 224Ra activities can be attributed to changes in fine-scale, phosphorite-bearing lithologies. The range of 223Ra/226Ra activity ratios is quite large (0.003–0.156) relative to the theoretical ratio of aged host rock, 0.046, indicating faster replenishment of 223Ra compared to 226Ra. The adsorption rate ranged from 0.03 to 2.4 min−1, corresponding to residence time of 0.4 to 33 min for Ra in groundwater. In contrast, the Ra desorption rate is slower, ranging from 0.5 to 21 × 10−4 min−1, which corresponds to a desorption time scale of 0.3–14 days. The retardation factor varied between (0.12 ± 0.03 and 7.0 ± 2.7) × 103. Within these samples, there was no significant correlation between the adsorption/desorption rate constants and the concentrations of redox-sensitive trace elements (i.e., Fe, Mn, or As), suggesting that redox processes alone do not control the adsorption–desorption constants. Furthermore, there is no apparent relationship between alkalinity and Ra adsorption-desorption rate constants, indicating that weathering processes alone do not control Ra sorption. The distribution coefficient varied between (0.16 and 9.3) × 103 L kg−1 (mean: 4.1 ± 4.0 × 103). This study provides insight into the adsorption–desorption kinetics of Ra within an aquifer controlled by fine-scale lithogenic and redox processes.